Causal Link between Trade, Political Instability, FDI and Economic Growth – Nigeria Evidence - AFOLABI, Luqman O.; ABU BAKAR, Nor Aznin (Journal of Economics Library, 2016)
Abstract. The current liberal policies adopted by the government in Nigeria since 1986 provided a stronger bilateral ties which continue to spring up between Nigeria and other participating trading partners, hence trade and foreign direct investment continue to increase noticeably on oil and gas sector. Nigeria continues to emerge as one of the biggest hubs for trade and investment in Africa while the free flow of FDI is expected to contribute and increase the exports rate. The last two decades witnessed numerous trade reforms, which has given more liberal export favorable surroundings. The pace of FDI is greater than the growth at international level, which would enhance grandness rational behind FDI inflow with the volume of trade and goods, as well as the possible effect of FDI inflow on the economic growth in Nigeria while not neglecting the likely effect of political instability that might pose to a major threat to foreign investors. An attempt is made to investigate the causal nexus between FDI inflow, volume of trade, political instability index, and Gross Domestic Product in Nigeria within the period of 1981 to 2012 using co-integration analysis and multivariate Granger causality. Multivariate Granger causality test is carried out using VECM approach to analyze the causal links among all the variables considered for estimation. A bi-directional causality was discovered between FDI inflow and economic growth (GDP); however there is one –way direction between political instability and FDI, between political instability and GDP. Moreover, there is also one –way relationship between FDI and volume of trade within the period of study. Keywords. FDI, Economic growth, Multivariate Granger causality test. JEL. F23, 016.